Development of Applications with Artificial Intelligence: Expert Perspectives and Recommendations - Julien Florkin (International Journal Software Engineering and Computer Science (IJSECS), 2025)
Artificial intelligence (AI) applications are accelerating significantly, supported by three pillars: core technologies, cost efficiency, and strategic direction. A comparative analysis reveals critical contributions from three technologies: (1) Machine Learning (ML) enhances user engagement by 35% through personalized recommendation systems on e-commerce platforms; (2) Natural Language Processing (NLP) reduces customer service operational costs by 47% via intelligent chatbots in the banking sector; and (3) predictive analytics improves cardiovascular disease diagnosis accuracy by 27% based on multicenter clinical data. Estimated AI application development costs range from $50,000 to $250,000, depending on algorithm complexity and computational infrastructure requirements. Future AI development will be shaped by two trends: (1) Edge AI, which reduces data processing latency by 60% through local computation, and (2) Explainable AI (XAI), which enhances algorithm transparency to comply with GDPR and ISO/IEC 23894 regulations. The study underscores that successful AI implementation requires multidisciplinary integration among data scientists, software engineers, and business stakeholders. Strategic recommendations include allocating 15–20% of R&D budgets for continuous learning, establishing an AI ethics committee aligned with OECD principles, and adopting an agile development model for market responsiveness